Emotion Regulation Strategies and Emotional Experiences in Blended EFL Contexts: A Case Study of Saudi University Learners - Mohamed Ali El Deen, Abdul Aziz Mohamed; Abdelwahab Mahmoud, Montasser Mohamed (Forum for Linguistic Studies, 2025)
This mixed-methods study examines how Saudi undergraduate EFL learners regulate their emotions within blended learning environments, in line with Saudi Arabia’s Vision 2030 educational reform goals. Drawing on Gross’s process model of emotion regulation and Pekrun’s control-value theory, the research collected data from 120 students via surveys, semistructured interviews, and reflective journals. Findings reveal that learners predominantly employ adaptive strategies such as cognitive reappraisal (68%), task-focused problem-solving (52%), and religious practices like prayer (74%). However, maladaptive approaches, including emotional suppression (61%) and avoidance (39%), remain prevalent, often shaped by cultural norms surrounding emotional restraint and gender roles. Emotional experiences were modality-dependent: online learning elicited higher anxiety (M = 3.8) due to technological disruptions and delayed feedback, whereas face-to-face settings promoted enjoyment (65%) through collaborative peer interaction. Cultural elements, particularly Islamic rituals and same-gender peer networks, were integral to learners’ emotional coping strategies. Despite these supports, students reported considerable technostress (63%) and disparities in digital access, which weakened their emotional resilience. The study underscores the importance of designing culturally responsive blended learning models that align with students’ religious and social realities. Practical recommendations include integrating faith-informed emotional support, gender-sensitive group structures, and enhanced digital infrastructure. These findings contribute to the development of inclusive pedagogical practices in Saudi and other Arab EFL contexts.